Effect of thermoplastic polyurethane (TPU) on the thermal and mechanical properties of polylactic acid (PLA)/ curcumin blends - Syed Shaharuddin, Sharifah Imihezri; Adnan, Muhammad Danial Afiq; Muhamad Khairussaleh, Nor Khairusshima; Mohd Shaffiar, Norhashimah; Buys, Yose Fachmi (IOP Publishing Ltd., 2018)
Polylactic acid (PLA) is known to be brittle by nature and thus limits the flexibility of the polymer. A possible solution to enhance the flexibility of PLA is to add a flexible polymeric based material such as thermoplastic polyurethane (TPU). In this study, 30-50 wt% of TPU was added into PLA/curcumin blends to improve its flexibility. Thermal analysis using differential scanning calorimetry shows that further additions of TPU at the expense of PLA did not affect the glass transition temperature, crystallisation temperature and melting temperature of the blends. Fibers of PLA/curcumin/TPU were successfully drawn and Single Fiber Tensile Test (SFTT) showed vast improvement in elongation at break. The initial addition of 30 wt% of TPU to the brittle PLA/curcumin composition causes a significant increase in elongation at break by 39 times and further additions at 50 wt %, the elongation at break increases by 105 times. However, with the increase in elongation, a decrease in strength and Young’s modulus was observed.